1988
DOI: 10.1111/j.1399-3054.1988.tb09214.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐dependent changes in ESR signals, NADPH oxidase and plasma membrane permeability in cotton roots

Abstract: Cakmak. 1. and Marschner, H. 1988. Zinc-dependent changes in ESR signals. NADPH oxidase and plasma membrane permeability in cotton roots. -Physiol. Plant. 73: 182-186.The effect of Zn2+ on the plasma membrane permeability and superoxide radical (O;-) formation in roots was studied with cotton (Gossypium hirsutum L. cv. Deltapine 15/21) plants grown in nutrient solution with different Znzt supply. Compared to Zn-sufficient plants, the plasma membrane permeability of Zn-deficient plants was increased as indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…2, this activity was greatly increased upon the addition of FeSO4, and was inhibited by the addition of catalase, as previously described in radish plasmalemma vesicles (Vianello and Macri 1989). The effect of catalase pointed out the presence of H202; the striking stimulation effect of NADH oxidation by ferrous ions could be explained by accounting for the formation of peroxide and superoxide ion radicals (Byczkowski and Gessner 1988;Cakmak and Marschner 1988;Halliwell and Gutteridge 1988;Vianello and Macri 1989). Ferrous ions would react with H20 z to give very reactive hydroxyl radicals ('OH) in a Fenton reaction (Vianello and Macri 1989).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…2, this activity was greatly increased upon the addition of FeSO4, and was inhibited by the addition of catalase, as previously described in radish plasmalemma vesicles (Vianello and Macri 1989). The effect of catalase pointed out the presence of H202; the striking stimulation effect of NADH oxidation by ferrous ions could be explained by accounting for the formation of peroxide and superoxide ion radicals (Byczkowski and Gessner 1988;Cakmak and Marschner 1988;Halliwell and Gutteridge 1988;Vianello and Macri 1989). Ferrous ions would react with H20 z to give very reactive hydroxyl radicals ('OH) in a Fenton reaction (Vianello and Macri 1989).…”
Section: Resultssupporting
confidence: 57%
“…The physiological role of these systems is still under discussion (Crane et al 1985, Komor et al 1987, Mr and Lin 1986. Evidence exists pointing out to the involvement of PMRS in iron reduction and uptake, and superoxide generation (Bienfait 1985, Cakmak and Marschner 1988, Crane et al 1991.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, deficiency of Zn has been reported to decrease activities of superoxide dismutases (SODs) (Cakmak et al, 1997;Yu et al, 1998;Yu and Rengel, 1999), particularly Cu/Zn-SOD that has Zn as its constituent . Deficiency of Zn is also reported to decrease activities of some other antioxidative enzymes like catalase (CAT) (Cakmak and Marschner, 1988), ascorbate peroxidase (APX) (Cakmak and Marschner, 1993;Yu et al, 1998), and glutathione reductase (GR) (Cakmak and Marschner, 1993). In contrast to these reports, our previous studies have shown an up-regulation in the activities of peroxidase (POD), APX, and GR in Zn-deficient wheat.…”
Section: Introductionmentioning
confidence: 71%
“…Cakmak (2000) has attributed much of the damage due to Zn deficiency of plants at the cellular level to the attack by reactive oxygen species (ROS). Loss of membrane integrity resulting from the attack of ROS is among the primary effects of Zn deficiency (Cakmak and Marschner, 1988). The redox reactions, particularly those involving electron transfer, lead to production of ROS like superoxide radical (O ÁÀ 2 ), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (OH Á ).…”
Section: Introductionmentioning
confidence: 99%
“…There are at least three convergent lines of evidence: (1) Zn2+ ions at concentrations higher than 20 pM completely inhibit plasma membrane ferricyanide reductase activity of Ehrlich ascites tumor cells(1g); (2) Cakmak and Mirschner (20) obtained results suggesting that Znz+ ions directly affect the integrity of cotton plasma membranes by interfering with superoxide generation by NADPH oxidase; and (3) Zn2+ ions have also been shown to inhibit selectively a H+ channel associated to the NADPH oxidase of n e~t r o p h i l s (~~) .…”
Section: Introductionmentioning
confidence: 99%